Left ventricular dysfunction in obese children and adolescents with nonalcoholic fatty liver disease. Issue 2 (23rd December 2013) - Pacifico, Lucia; Di Martino, Michele; De Merulis, Antonio; Bezzi, Mario; Osborn, John Frederick; Catalano, Carlo; Chiesa, Claudio
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease (NAFLD) may increase the risk for cardiac dysfunction. The present study aimed to determine whether, in children, NAFLD is associated with subclinical left ventricular (LV) structural and functional abnormalities independently of metabolic risk factors. We performed a complete echocardiographic study including tissue Doppler imaging, magnetic resonance imaging (MRI) for measurement of hepatic fat fraction (HFF) and abdominal fat mass distribution, along with lipid profile, insulin sensitivity, and high‐sensitivity C‐reactive protein in 108 obese children, 54 with (HFF ≥5%) and 54 without NAFLD, and 18 lean healthy subjects. The three groups were matched for age, gender, and pubertal status, and obese children with NAFLD were matched for body mass index/standard deviation score with those without NAFLD. Forty‐one of the children with NAFLD underwent liver biopsy. Compared to controls and children without liver involvement, those with NAFLD had features of LV diastolic dysfunction, including higher E‐to‐e' ratio and lower e' tissue velocity. The Tei index (reflecting the combined systolic and diastolic LV function) was also significantly higher in NAFLD children. Among children with biopsy‐proven NAFLD, 26 had definite nonalcoholic steatohepatitis (NASH) and 15 were not‐NASH. Patients with definite‐NASH had significantly lower e' velocity and significantly higher E‐to‐e' and Tei index (P < 0.001, respectively) than those without NASH. In multiple logistic regression analysis, NAFLD was the only statistically significant variable associated with increased E‐to‐e' ratio, whereas NAFLD and systolic blood pressure were significantly associated with increased Tei index. Conclusion: Asymptomatic obese children with NAFLD exhibit features of early LV diastolic and systolic dysfunction, and these abnormalities are more severe in those with NASH. (Hepatology 2014;59:461–470)